Combined Staged Endoscopic and Microsurgical Approach of a Third Ventricular Choroid Plexus Papilloma in an Infant - Reddy, D.; Gunnarsson, T.; Scheinemann, K.; Provias, J. P.; Singh, S. K. (min - Minimally Invasive Neurosurgery, 2011)
Choroid plexus papillomas of the third ventricle in newborn infants are quite rare and present a significant surgical challenge. This case report illustrates the utility of endoscopy in facilitating tumor resection.A 6-week-old boy, born prematurely at a gestational age of 35 weeks, presented with hydrocephalus secondary to a choroid plexus papilloma in the third ventricle, extending to the aqueduct of Sylvius and into the fourth ventricle. On admission, he was found to have clinical signs of raised intracranial pressure. MRI revealed a homogeneously enhancing mass primarily in the third ventricle. The initial surgical procedure was insertion of a ventriculo-peritoneal shunt, followed by an endoscopic biopsy, which allowed the surgeons to mobilize the tumor into the right lateral ventricle. This facilitated a subsequent transcortical approach to completely remove the tumour.The authors present a case of choroid plexus papilloma in an uncommon location with a unique surgical approach and a successful outcome with no neurological deficits. We detail our surgical approach and the complexity of approaching a tumor located in the third ventricle of an infant.
Keywords: choroid plexus papilloma; hydrocephalus; neuro-endoscopy; third ventricle